2020
DOI: 10.12659/msm.921811
|View full text |Cite
|
Sign up to set email alerts
|

Does Type of Menopause Affect the Sex Lives of Women?

Abstract: The aim of this study was to investigate factors affecting the sex lives of middle-aged women, and whether surgical menopause affects sexual function differently from natural menopause, by comparing effects on sexual performance of women with similar demographic features. Material/Methods:The study included 151 women with surgical menopause (SM), 357 women with natural menopause (NM), and 186 perimenopausal women (PM). The women were asked to complete a 6-question survey of sexual performance parameters. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…During both menopause and premenopause, women experience several problems with their sexual life due to endocrinological and physiological changes, such as decreased sex hormones and urogenital atrophy. 38 According to the present results, considering different domains of sexual function, about half of participants had good desire, about half had good arousal, almost more than a third had good lubrication, almost more than a half had good orgasm, nearly zero percent had no pain, and about half were satisfied. Also, the highest mean score belonged to the dimension of ssatisfaction, which was unfavorable, and the lowest mean score belonged to the dimension of pain, which was almost favorable.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…During both menopause and premenopause, women experience several problems with their sexual life due to endocrinological and physiological changes, such as decreased sex hormones and urogenital atrophy. 38 According to the present results, considering different domains of sexual function, about half of participants had good desire, about half had good arousal, almost more than a third had good lubrication, almost more than a half had good orgasm, nearly zero percent had no pain, and about half were satisfied. Also, the highest mean score belonged to the dimension of ssatisfaction, which was unfavorable, and the lowest mean score belonged to the dimension of pain, which was almost favorable.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, the reasons for the difference between this study and the present study are differences in personal factors, interpersonal relationships, and social and family traditions. During both menopause and premenopause, women experience several problems with their sexual life due to endocrinological and physiological changes, such as decreased sex hormones and urogenital atrophy 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of sexual function and menopausal type studies in the literature are also supported by our study. For example, in the study published by Bıldırcın et al in 2020 [20], it was shown that there was no significant difference regarding sexual function in patients with surgical menopause compared to patients with natural menopause. This finding corresponds to the result of our study.…”
Section: Discussionmentioning
confidence: 99%